Comparison of the Effectiveness of Dialectical Behavior Therapy and Meichenbaum-Based Cognitive Therapy on Fear of Negative Evaluation in Students with Social Anxiety Disorder - Toori, Fatemeh; Mahdian, Hossein; Bakhshipour, Abolfazl (Iranian Journal of Neurodevelopmental Disorders, 2025)
Purpose: The present study aimed to compare the effectiveness of Dialectical Behavior Therapy (DBT) and Meichenbaum-based Cognitive Therapy in reducing fear of negative evaluation in students with social anxiety disorder.Methods and Materials: This study employed a quasi-experimental design with a pretest-posttest control group and a two-month follow-up. The statistical population consisted of female lower secondary school students in the Tabadkan district of Mashhad during the 2023–2024 academic year. From this population, 45 students diagnosed with social anxiety were selected using purposive sampling and were randomly assigned into two experimental groups and one control group (15 participants per group). The first experimental group received eight 60-minute sessions of Dialectical Behavior Therapy, while the second experimental group received ten 60-minute sessions of Meichenbaum-based Cognitive Therapy. The control group received no intervention throughout the study. The research instrument was the Fear of Negative Evaluation Questionnaire by Watson and Friend (1969), which was administered as a pretest, posttest, and follow-up measure across all three groups. The data were analyzed using SPSS-26 software, employing repeated measures analysis of variance (ANOVA) and post-hoc tests.Findings: The results indicated that both therapeutic methods significantly reduced fear of negative evaluation, and there was no significant difference between the two interventions (p < 0.005).Conclusion: Based on these findings, it can be concluded that both Dialectical Behavior Therapy and Meichenbaum-based Cognitive Therapy are effective in reducing fear of negative evaluation. Therefore, either approach can be used to assist students with social anxiety disorder.